Pharmacodynamics of current and emerging PD-1 and PD-L1 inhibitors for the treatment of non-small cell lung cancer. (1st February 2020) - Rocco, Danilo; Malapelle, Umberto; Del Re, Marzia; Della Gravara, Luigi; Pepe, Francesco; Danesi, Romano; Troncone, Giancarlo; Gridelli, Cesare
ABSTRACT: Introduction : As of today, one of the cornerstones of NSCLC treatment is represented by Immune Checkpoint Inhibitors (ICI) treatment in the form of anti-PD-1/PD-L1 monoclonal antibodies. However, apart from currently approved, recommended and employed agents (nivolumab, pembrolizumab, atezolizumab, durvalumab), several new agents are currently under development and investigation both in monotherapy and in combinational settings. Areas covered : This paper aims to discuss both the current state of the art and the most interesting emerging PD-1 and PD-L1 inhibitors and their present and future role in metastatic NSCLC treatment. Expert opinion : Great scientific interest lies in combinational settings, involving both already developed FDA and EMA approved and not approved agents and anti-PD-1 and PD-L1 inhibitors, that will certainly provide data about pharmacodynamic and clinical properties of these associations, enhancing our understanding of ICIs and cancer immunotherapy. Moreover, new potential predictive biomarkers are much needed, especially considering the less decisive role of PD-L1 in treatment algorithms involving chemo-immune combinations and the current lack of other validated predictive biomarkers.